Fire-fighting UAV with shooting mechanism of fire extinguishing ball for smart city - Nastaran Reza Nazar Zadeh; Ameralden H. Abdulwakil; Mike Joshua R. Amar; Bernadette Durante; Christian Vincent Nico Reblando Santos (Institute of Advanced Engineering and Science, 2021)
With the growth of technology and massive city development, firefighting services have become more challenging to cope with a smart-city concept. One of the challenges that firefighters are facing is reaching the top floors of high-raised buildings. Firefighters need heavy and oversized pieces of equipment to reach top floors, which they sometimes fail to deliver on time due to big cities' traffic. The proposed solution to this global problem is using firefighting unmanned aerial vehicle (UAV) to reach the top floors fast and efficiently; It can also provide a better vision for the firefighting team and slow down the spread of fire using fire extinguishing ball. In this paper, a noble design for a Firefighting UAV with shooting and dropping mechanism of fire extinguishing ball has been developed and successfully tested. A Camera with night vision has been integrated into the UAV to provide a helpful aid for firefighters. The UAV has a controller with a 2.4 GHz radio frequency (RF) signal and video surveillance to regulate the UAV's movement. The controller is also for activating the shooting and dropping mechanism. The researchers examined the behavior of the drone in terms of its stability and functionality.